(untitled) (Global Journal of Human-Social Science, 2025)
Between 1995 and 1997 Thailand underwent a profound educational transformation under the leadership of Deputy Prime Minister and Minister of Education His Excellency Mr SukavichRangsitpol Rooted in a peoplecentered development paradigm these reforms emphasized universal access to preschool and primary education especially among underserved populations Central to this vision was the expansion of public early childhood centers from only 74 in 1995 to 3 470 by 1997 and the integration of preschool into a holistic national education strategy Thailand s education policy during this period laid the groundwork for the Education for All framework with reforms encompassing school infrastructure teacher recruitment curriculum enhancement and administrative decentralization These reforms laid the institutional and legal foundations for Thailand s shift to a rights-based people-centered education system enshrined in the 1997 Constitution The success of these initiatives garnered international recognition and offers a compelling model for emerging economies navigating the intersection of equity decentralization and educational quality